Effects of Home Exercise Promoting Program Using a Stretched Rubber Band on the Physical Fitness of the Elderly - Thinchana, Naichanok; Naka, Kanittha; Srikaew, Maithai (Journal of Research in Nursing-Midwifery and Health Sciences, 2018)
This quasi-experimental, time series design, study aimed to determine the effects of a home exercise promotion program using a stretched rubber band on the physical fitness of twenty-eight elders. The study period was 12 weeks divided into two stages: a control period (week 1-6) the subjects performed activities as usual, and an experimental period (week 7-12). During the experimental period, the subjects received a home program to promote physical exercise which adopted the 5 process behavior modification framework of Prochaska and Declemente with the application of exercise using a rubber band based on the FITTE Principle. Research instruments consisted of 1) experimental instruments including a home exercise promotion program using a stretched rubber band, and a handbook for the home exercise program using a stretched rubber band and 2) data collection instruments including a general information questionnaire, an exercise recording form, and the Sports Authority of Thailand Physical Fitness Test. The instruments were validated by three experts. The reliability of physical fitness test was examined by using a test-retest method which yielded the correlation coefficient of 0.9. General information data were analyzed using frequency, percentages, mean, and standard deviation, and hypothesis was tested using repeated measures analysis of variance. Results revealed that the elderly’s physical fitness in relation to muscular strength and endurance, muscular flexibility, and lung and heart endurance after participating in the home exercise promotion program using a stretch rubber band (week 12) was statistically significantly higher than that of before participating in the program (week 1- 6) (p<. 05). Finding of this study showed that the home exercise promotion program using a stretched rubber band improved a physical fitness and should be implemented in the elderly at home.